2020
DOI: 10.26434/chemrxiv.13038236.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anticancer Mechanism of Withania Somnifera and Its Bioactive Compounds : A Short Review Along with Computational Molecular Docking Study

Abstract: <p>Withania somnifera, known as Aswogondha in Bangladesh and some part of India, is a shrub of Solanceae family. Parts of this plant is used as alternative medicine in this region to cure diseases from bronchitis to insomnia. Although such use of the plant is not supported by clinical research, recent studies have found anticancer activity of some proteins derived from w. somnifera. The purpose of this study is to summarize the anticancer activity of medicinal plant Withania somnifera and its bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The anticancer potential of W. somnifera has been mainly attributed to Withanolide and Withaferin A, which are two principal phytochemicals from this plant. In vivo , in mice, it was reported that W. somnifera , through the activities of Withanolide and Withaferin-A, modulate different signalling pathways such as apoptosis, autophagy and reactive oxygen species (ROS) pathways ( Shikder et al, 2020 ). In male Swiss albino mice, extracts from W. somnifera were shown to inhibit lung adenoma ( Senthilnathan et al, 2006a ) while the root extracts of this plant were shown to prevent ROS-induced injury in model mice ( Senthilnathan et al, 2006b ).…”
Section: Traditional African Medicinal Plants Used In the Management ...mentioning
confidence: 99%
“…The anticancer potential of W. somnifera has been mainly attributed to Withanolide and Withaferin A, which are two principal phytochemicals from this plant. In vivo , in mice, it was reported that W. somnifera , through the activities of Withanolide and Withaferin-A, modulate different signalling pathways such as apoptosis, autophagy and reactive oxygen species (ROS) pathways ( Shikder et al, 2020 ). In male Swiss albino mice, extracts from W. somnifera were shown to inhibit lung adenoma ( Senthilnathan et al, 2006a ) while the root extracts of this plant were shown to prevent ROS-induced injury in model mice ( Senthilnathan et al, 2006b ).…”
Section: Traditional African Medicinal Plants Used In the Management ...mentioning
confidence: 99%
“…It is a traditional Southeast Asian medicine that is commonly utilized in India. It has anti-inflammatory, analgesic, antipyretic, antidiabetic, hepatoprotective, hypolipidemic, antistress, and immunomodulatory properties, according to scientific studies [9]. Some of its phytochemicals, such as eugenol, rosmarinic acid, apigenin, myretenal, luteolin,-sitosterol, and carnosic acid, have been shown in preclinical studies to prevent chemical-induced skin, liver, oral, and lung cancers and to mediate these effects by increasing antioxidant activity, altering gene expressions, inducing apoptosis, and inhibiting angiogenesis and metastasis [9].…”
Section: Ocimum Tenuiflorummentioning
confidence: 99%